Access 2013 intermediate - Christie, Jason; Safari eBooks ([Place of publication not identified] : [CompuWorks], 2016)
"This course is designed to teach students intermediate level skills in Microsoft Access 2013. In this course, students will learn to design tables for improved accuracy in data entry by setting default values and restricting data entry, review the various options to share data with other applications including Word and Excel, learn about Action Queries to automate updating, appending and deleting table data, and review various advanced query techniques such as using Query Joins, Parameter queries, working with totals and Crosstab queries. Students will also learn how to automate processes with Macros, advanced form techniques using Conditional Formatting, Tab controls, Combo Box controls and Sub-Forms, and advanced report techniques using Sub-Reports, columns and inserting charts."--Resource description page.
Presenter, Jason Christie.
Title from title screen (viewed September 29, 2016).
Imprint from resource description page.
Keywords: Microsoft Access; Database management; Electronic books